Vertical jump performance in hungarian male elite junior soccer players. - Petridis, L.; Utczás, K.; Tróznai, Z.; Kalabiska, I.; Pálinkás, G.; Szabó, T. (Research Quarterly for Exercise and Sport, 2019)
Purpose: Vertical jump is a common test to measure impulsive ability in soccer; however, limited normative data have been published on young soccer players from vertical jump measurements on a force platform. The purpose of this study was to provide normative values for three chronological age groups of male junior soccer players (U16, U17 and, U18 years). Method: Vertical jump performance of 365 soccer players (16.4 ± 0.8 years) was assessed using a force platform measurement system. Net impulse, force, power, jump height (impulse-momentum), jump height (flight time) were reported for each age group for squat jump (SJ) and countermovement jump (CMJ). Results: Mean values ± SD of jump height were 32.9 ± 4.1, 33.5 ± 4.0, and 33.9 ± 4.2 cm for the three age groups respectively in SJ and 36.3 ± 3.8, 37.5 ± 3.9, and 38.6 ± 4.4 cm in the CMJ. Mean values of all age groups for maximum force and maximum power were 1559 ± 211 N and 3261 ± 492 watt respectively for SJ and 1598 ± 241 N and 3287 ± 502 watt for CMJ. Based on descriptive data, percentiles were reported for all examined variables. Conclusions: Jump height and relative values were less sensitive discriminator variables between age groups in the studied age range, while maximum impulse, maximum force, and maximum power were more sensitive to changes in maturational status. Normative values can be used by the coaches in the interpretation and evaluation of their athletes' performance and for training and talent identification purposes.